Computer-Assisted Cognitive Remediation in Schizophrenia: Efficacy of an Individualized vs. Generic Exercise Plan - Bossert, Magdalena; Westermann, Celina; Schilling, Thomas M.; Weisbrod, Matthias; Roesch-Ely, Daniela; Aschenbrenner, Steffen (Frontiers in Psychiatry, 2020)
Computer-Assisted Cognitive Remediation (CACR) is an economical, adjustable and effective treatment for individuals with schizophrenia. The current randomised controlled study examined whether an individualised or generic exercise plan in CACR is superior in patients with multiple cognitive deficits compared to treatment-as-usual (TAU). Fifty-nine inpatients diagnosed with schizophrenia were randomly assigned to (1) TAU, (2) TAU plus an individualised exercise plan in CACR or (3) TAU plus a generic exercise plan in CACR. Neuropsychological performance, psychopathology and functional outcome were assessed at baseline and post-treatment. The results show a medium to large training effect for all neuropsychological performance measures. Contrary to our expectations the neuropsychological improvement over time did not differ between groups. Self-reported depression, global level of functioning and activity and participation functioning showed a significant improvement from baseline to post treatment. However no further group, time or interaction effects for other psychopathology and functional outcome could be demonstrated. Possible implications for clinical use of CACR and future studies are discussed.